2020
DOI: 10.1111/cch.12745
|View full text |Cite
|
Sign up to set email alerts
|

Exploring health professionals' understanding of evidence‐based treatment for idiopathic toe walking

Abstract: Background Idiopathic toe walking (ITW) is an exclusionary diagnosis resulting in a child walking on the balls of their feet. Preferred treatment options may be due to the severity of the toe or the health professional preference There are limited guidelines supporting consistent treatment recommendations for this condition. This research aimed to understand agreement between health professionals' knowledge of evidence for common treatment strategies for ITW and if health professionals supported these strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
(48 reference statements)
1
30
0
Order By: Relevance
“…With limited literature guiding treatment approaches and resources, these differing backgrounds likely affected what treatment was offered. 10 For example, a physical therapist may be more apt to consider the use of AFOs, sensory integration strategies, stretching, and casting as they are expertly trained in these modalities. 10 Surgeons may be more apt to abandon nonoperative modalities earlier if success is not achieved and consider surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With limited literature guiding treatment approaches and resources, these differing backgrounds likely affected what treatment was offered. 10 For example, a physical therapist may be more apt to consider the use of AFOs, sensory integration strategies, stretching, and casting as they are expertly trained in these modalities. 10 Surgeons may be more apt to abandon nonoperative modalities earlier if success is not achieved and consider surgery.…”
Section: Discussionmentioning
confidence: 99%
“…10 For example, a physical therapist may be more apt to consider the use of AFOs, sensory integration strategies, stretching, and casting as they are expertly trained in these modalities. 10 Surgeons may be more apt to abandon nonoperative modalities earlier if success is not achieved and consider surgery. Additionally, surgeons may be seeing the most severely affected children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, described in a recent international health professional's survey. 11 Without international uniformity of treatment pathways, parents and children may continue to receive disparate care. It should be a priority for healthcare providers and researchers to provide information consistent with evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of treatment options for ITW found that healthcare professionals preferred up to 10 different treatments and these varied depending on the healthcare professional. 11 For parents, varied treatment options may result in a misinterpretation of an ITW diagnosis, its natural history or why their child received a different treatment to those offered to other children with the same diagnosis.…”
Section: Introductionmentioning
confidence: 99%